(untitled) - Dawkins, Richard (New York, 2006)
The full explanatory power of the gene's eye view was presented, in fine non-technical prose, for the first time in one short volume, bringing novel insights to those working in the field and inspiring whole new areas of research. Yet even that is not all. It has been widely acclaimed too for its literary qualities. Here is a book that set a new standard in science writing for the wider public, a modern masterpiece that fresh generations of aspiring young scientists would seek to emulate.
Keywords: Genetics,Di truyền học